(untitled) (Papeles, 2022)
Introduction: The challenges of teacher training in mathematics in Brazil led to the structuring of a theoretical framework that would support the teacher’s work, and that would consider the obstacles experienced by teachers in their practice. With this, the Professional Didactic Situation (SDP) is presented, a proposal of complementarity between the Professional Didactics (DP) and the Theory of Didactic Situations (TSD), with a view to the formation of the mathematics teacher. Thus, the objective of the present work is to present, through didactic situations, a proposal of practical characterization for the concept of Professional Didactic Situation (SDP). Methodology: To achieve this objective, a bibliographic research was chosen, which supported the construction of the theoretical framework and the development of two professional didactic situations. Discussion: The professional didactic situations were organized from the identification of professional obstacles of the mathematics teacher, especially in the context of the polynomial functions of the 1st grade, as well as the potentialities of these situations were discussed. Conclusion: It was possible to understand, therefore, that the SDP is directly related to the observation of professional obstacles, embodied in the field of activity of the mathematics teacher (classroom, work plan and teaching system), with a view to to the development of an effective action (modeled through pragmatic concepts).